Balanço e eficiência de uso de nutrientes em sistemas de produção de grãos na região Oeste do Paraná - Madalosso, Tiago (2015)
In Brazil it is possible for two or more per year grain crop cultivation, but there is evidence that the cultivation tillage system with only commercial crops has resulted in soil degradation. The objective of this study was to evaluate the balance and efficiency of use of N, P and K, the effect on the chemical properties of soil and biometric variables of crops in grain production systems in western Parana region, encompassing different fertilization and probate cultures. The experiment was designed in randomized blocks with the treatments arrangement in divided plots with 4 repetitions. In the plots were installed the winter successions (5), wheat, oats, sunn hemp, corn second crop + brachiaria and corn 2nd harvest and the subplots fertilizers (3) organic, organomineral and mineral. The summer crop was planted to soybeans. The test was conducted for three seasons, starting with the planting of soybeans in 2013. Soil samples were collected after the 3rd growing at 0-10 and 10-20 cm. In the first crop, the use of organic fertilizer promoted increase in grain yield, mass of thousand grains, at the height of soybean plants, the bedding, the number of pods per plant, increased the leaf content and export of N by grain soybeans. In the third crop, there were no differences between the fertilizer and succession to black oat and sun hemp provided higher-yielding soybeans. The oat presented the highest dry matter yield, higher concentration of P in the shoot and greater extraction of N, P and K. Corn consortium + brachiaria reduced the yield of maize grain compared to monocrop. The application of poultry litter and the use of oat or crotalária as cover crops in winter, provide increased grain yield for the soybean crop. Using the same dose of P and K there is no difference in the yield of soybeans, corn and wheat between mineral fertilizers and organomineral. A use of poultry litter promotes increase of soil P and K soil, but does not increase the levels organic matter. P and K use efficiency is higher in soy succession - 2 nd harvest corn. The efficiency of use of N, P and K is lower in the fertilizer with organic fertilizer. There is no difference in the use efficiency of P and K between organomineral and mineral fertilizers, as for N, the mineral fertilizer has higher efficiency. ON was the nutrient with the most negative balance in the soil and the use of cover crops (black oats and crotalaria) increases the N balance in the soil. OP showed balance in the soil near zero being lower in succession with wheat and oats. The K balance in the soil was negative and was not different between the tested grain and fertilizer production systems